Pore system and methane adsorption capacity features of marine and marine-continental transitional shale in the Sichuan Basin, SW China - Wang, Enze; Guo, Tonglou; Dong, Xiaoxia; Wang, Tong (Frontiers in Earth Science, 2023)
Recently, significant achievements have been made in the gas exploration of marine Longmaxi shale in China. As exploration efforts have advanced, the exploration targets have gradually expanded to other sedimentary systems (marine-continental transitional and lacustrine). Compared with marine shale, shale in other sedimentary systems shows stronger heterogeneity, rendering previous exploration experiences of marine shale ineffective in guiding exploration efforts. Therefore, there is a pressing need for comparative studies to support future exploration practices. In this paper, the marine Longmaxi Formation and the marine-continental transitional Longtan Formation shales in the Lintanchang area of the southeastern of the Sichuan Basin are selected as the research objects. The study aims to compare the mineralogical characteristics, pore systems, and methane adsorption capacities of these two sets of shales, thereby revealing the differences in controlling factors that affect their physical properties and methane adsorption capacities. Our results show that the Longtan shale exhibits a higher clay mineral content, while the Longmaxi shale demonstrates significantly higher siliceous mineral content. Compare with Longmaxi shale, the Longtan shale exhibits a wider distribution range and higher average value of TOC content. The pore system in the Longmaxi shale is primarily dominated by organic matter-related pores, whereas the Longtan shale is characterized by clay mineral-related pores as the primary pore type. Given the variance in sedimentary environments, the controlling factors of physical properties differ significantly between the two sets of shales. In the case of the Longmaxi shale, TOC content is the most influential factor governing physical properties, while clay mineral content exerts the most significant influence on physical properties in the Longtan shale. Furthermore, TOC content emerges as the primary factor affecting methane adsorption capacity in both the Longmaxi and Longtan shales, despite the presence of significant variations in their pore systems. Nevertheless, the specific mechanisms through which TOC content impacts methane adsorption capacity exhibit variations between the two distinct shale types under investigation. The difference in sedimentary environment leads to various effects of mineral composition on methane adsorption capacity. Therefore, in the future research, the influences of different factors on methane adsorption capacity should be studied in combination with the sedimentary background.